1999
DOI: 10.1002/1531-8249(199901)45:1<124::aid-art19>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Acute cerebellitis caused byCoxiella burnetii

Abstract: We report a childhood case of severe acute cerebellitis caused by Coxiella burnetii. After 10 days of fever and headache, the patient fell into a drowsy state. Examination of the cerebrospinal fluid (CSF) revealed pleocytosis, an increased level of protein, and negative results in bacterial and viral studies. Magnetic resonance imaging demonstrated a herniated tonsil compressed by the swollen vermis. Administration of minocycline relieved the patient's clinical symptoms. C. burnetii was isolated from the CSF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 18 publications
1
31
0
3
Order By: Relevance
“…Cerebellar encephalitis is mentioned in literature but very seldomly. 55 Some studies have mentioned similar cases: Bernit et al reported a case of paresis of the oculomotor nerve, 39 Ropper et al and Sawaishi et al each mentioned a case of acute cerebellitis 55,56 and an English study also reported a case of cerebellar ataxia. 57 Cutaneous lesions occur in 5-21% of acute Q fever cases, 9,58 usually in the form of a transient punctuate rash, a maculopapular rash, or, more rarely, erythema nodosum.…”
Section: Discussionmentioning
confidence: 98%
“…Cerebellar encephalitis is mentioned in literature but very seldomly. 55 Some studies have mentioned similar cases: Bernit et al reported a case of paresis of the oculomotor nerve, 39 Ropper et al and Sawaishi et al each mentioned a case of acute cerebellitis 55,56 and an English study also reported a case of cerebellar ataxia. 57 Cutaneous lesions occur in 5-21% of acute Q fever cases, 9,58 usually in the form of a transient punctuate rash, a maculopapular rash, or, more rarely, erythema nodosum.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately two-thirds of CSF analyses show increased numbers of leukocytes, typically mononuclear, and one-third of specimens had increased protein levels (38). C. burnetii is difficult to culture from the CSF but has been identified by PCR in one patient (338). One necropsy of a patient who died of Q fever pneumonia showed small perivascular hemorrhages in the brain, with capillary endothelial swelling without perivascular accumulation of leukocytes (406).…”
Section: Rickettsiaceaementioning
confidence: 99%
“…In a review of 122 cases, the neurological signs were classified as follows, in order of decreasing frequency: supranuclear ophthalmoplegia, confusion and dementia, psychiatric signs, myoclonic signs, seizures, hypothalamic involvement, cerebellar forms, myorhythmic forms, cranial nerve involvement, peripheral neuropathies, and spinal cord involvement (129). Meningeal involvement is often associated with all these neurological signs, so that the disease is 338 DREVETS ET AL. CLIN.…”
Section: Tropheryma Whippleimentioning
confidence: 99%
“…Menos freqüentemente podem ocorrer sinais meníngeos e crises convulsivas 4 . Casos mais severos, associados à hipertensão intracraniana, podem simular um tumor de fossa posterior ou mesmo apresentar-se como hidrocefalia aguda 5,6 .…”
Section: Discussionunclassified
“…Infecções bacterianas também têm sido associadas a cerebelite, incluindo Mycoplasma pneumoniae, Borrelia burgdorferi, Legionella e Coxiella burnetti. Além disso, a cerebelite pode ocorrer após imunizações para hepatite, varíola e caxumba ou mesmo sem nenhum fator etiológico 4,7 .…”
Section: Discussionunclassified